The Landscape of DNA Methylation Generates Insight Into Epigenetic Regulation of Differences Between Slow-Twitch and Fast-Twitch Muscles in Pseudocaranx dentex - Li, Busu; Wang, Huan; Li, Ang; An, Changting; Zhu, Ling; Liu, Shufang; Zhuang, Zhimeng (Frontiers in Marine Science, 2022)
Skeletal muscles of teleost are mainly composed of slow-twitch muscles (SM) and fast-twitch muscles (FM), differed in contractile properties, metabolic capacities, and regeneration rate. The transcriptional regulatory mechanisms that control different muscle types have been elucidated in teleost according to transcriptome between SM and FM. However, the differences between SM and FM were not only affected by genotype, but also by complicated epigenetic effects, including DNA methylation which usually regulates genes in transcription level. To determine the essential role of DNA methylation in the regulation of different muscle types, we analyzed whole genome methylation profiles of pelagic migratory fish Pseudocaranx dentex with abundant and well-separated SM, and integrated DNA methylation profiles with the previously obtained transcriptome data. A total of 4,217 differentially methylated genes (DMGs) were identified, of which 3,582 were located in the gene body and 635 in the promoter. These DMGs mainly participated in muscle metabolite and cell junction. Enriched cell junction pathway reflected different capillary distribution between SM and FM. Through comprehensive analysis of methylome and transcriptome, 84 differentially expressed genes (DEGs) showed significant methylation variation in promoters between SM and FM, indicating their expression were regulated by DNA methylation. Hypomethylated and highly-expressed oxygen storage protein Myoglobin (myg) in SM indicated demethylation of myg promoter could up-regulate its expression, thus increasing O2 supplying and meeting oxygen demands of SM. Hypermethylated and lowly-expressed tnn (Troponin) and rlc (Myosin Regulatory Light chain) in SM may be associated with low mobility of myosin cross bridges, which lead to slower and less frequent muscle contraction in SM than in FM. In addition, hypomethylated and highly-expressed lbx1 (Ladybird homeobox protein homolog 1) and epo(Erythropoietin) may be related to increased satellite cell numbers, and Semaphorin/Plexin genes may be related to higher rate of neuromuscular connection reconstruction, which further promote high muscle regeneration efficiency in SM. Our study elucidated the potential DNA methylation mechanisms that regulate physiological characteristics differences between SM and FM which could facilitate our understanding of skeletal muscle adaptation in pelagic migratory fishes and further enrich the theoretical basis for the study of physiological characteristics and adaptive evolution in teleost fishes.